2019
DOI: 10.1080/0966369x.2019.1611545
|View full text |Cite
|
Sign up to set email alerts
|

The exploitation narratives and coping strategies of Ethiopian women return migrants from the Arabian Gulf

Abstract: A large number of unskilled women from least developed countries engage in international migration as domestic workers. Although the transnational migration experiences of these women could potentially be empowering, women migrants are vulnerable to exploitation. This paper explores the migration experiences of Ethiopian women who migrate to Arabian Gulf countries as domestic workers under the kafala labor sponsorship system and how they cope with their traumtic experiences upon return to Ethiopia. Forty-eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 37 publications
1
28
0
1
Order By: Relevance
“…Few studies examined the coping strategies of Ethiopian migrant returnees [ 27 , 28 , 43 ]. Ethiopian women migrants to the Middle East use different coping strategies while they are working as housemaids in Arabian countries and after their homecoming [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies examined the coping strategies of Ethiopian migrant returnees [ 27 , 28 , 43 ]. Ethiopian women migrants to the Middle East use different coping strategies while they are working as housemaids in Arabian countries and after their homecoming [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Few studies examined the coping strategies of Ethiopian migrant returnees [ 27 , 28 , 43 ]. Ethiopian women migrants to the Middle East use different coping strategies while they are working as housemaids in Arabian countries and after their homecoming [ 27 ]. Women migrants use problem-focused coping mainly escaping from employer’s house, and emotion-focused coping principally praying or crying to manage distress they face abroad, and sense-making and benefit-seeking to cope with traumatic experiences.…”
Section: Introductionmentioning
confidence: 99%
“…The migration experience of domestic workers in the Arabian Gulf and Middle East often entails physical, psychological, and sexual abuse (Jureidini & Moukarbel, 2006). More than half of our participants experienced sexual violence in the destination countries, perpetrated either by their Arab employer or Ethiopian agent (see also, Nisrane et al, 2019). On the one hand, sexually abused Ethiopian women are typically pictured as exploited beings and sexual objects, who do not deserve love and care, and who are not a good prospect for marriage (see also De Regt & Tafesse, 2016).…”
Section: Discussionmentioning
confidence: 97%
“…Our study found that some returnees involve in sex work to help their family in the home country or sustain themselves in destination countries. Many of the returnees regret that they spent their young age trying to get money to help their parents and siblings by compromising their own future life in both economic and social terms (see also Grabska et al, 2019aGrabska et al, , 2019bNisrane et al, 2017Nisrane et al, , 2019. To this end, Grabska et al (2019b) stress positive changes that occur through migration are often slow and negative impacts outweigh the positive ones in young girl migrant's life.…”
Section: Discussionmentioning
confidence: 99%
“…With specific reference to those fleeing the multiple waves of violence in Sri Lanka, Valenta and Jakobsen (2018: 31) state that ‘the Gulf region seems especially to have attracted those who could not or did not want to seek protection in the West during the war’. Despite the widely criticised position of labour migrants within these states (Silvey, 2004; Buckley, 2013; Kathiravelu, 2012; Nisrane et al, 2019), the latter option – of people who ‘did not want to seek protection’ elsewhere – evidences a group of individuals who intentionally sought opportunities within the Gulf that allowed them to avoid applying for asylum elsewhere. Katz’s (2001) work describes how young men from the village she studied in Sudan would journey, often illegally, to the Gulf States in order to escape forced conscription and repressive government policies.…”
Section: Global Geographies Of Displacement and Refugementioning
confidence: 99%